Optimization of new semi-automatic TIG welding process for surface quality through taguchi method - Hamjah, Mohd Khairulamzari (2014)
Tungsten inert gas (TIG) welding which uses a non-consumable tungsten electrode and an inert gas for arc shielding, is an extremely important arc welding process. The aims of this research project are to find optimization parameters in weld bead using TIG. Semi-automatic TIG was developed to ensure the success of this research project. Samples are produce in single bead and padding bead on top of substrate (base metal) in horizontal position. Substrate material is from Mild Steel AISI 1018 while wire filler ER70S-6 has a diameter of 0.8 mm and Tungsten electrode EWth-2 (2% Thorium, Red) has a diameter 2.4mm. Argon is used as shielding gas for this research project. Parameters such as Ampere (A), Travel Speed (mm/s) and Wire Feed Rate (mm/min) has been determined and selected as factors that can influence the weld bead result. Taguchi orthogonal array L9 (Minitab 16) was used to determine the amount of runoff and the analysis of samples. The result for surface roughness was found to be better with an average value of Ra 2.96 µm for single bead and Ra 3.08 µm for padding bead when compared to the work of other researchers. Surface hardness has also shown improvement from this research project. Analysis result shows that the travel speed of the torch has the greatest effect on surface roughness followed by wire feed rate and ampere. Dye Penetrant Inspection (DPI) interpretations of the nearest Optimize level shows no cracks or porosity occurring on top of the bead surface. Defects only happen at the undercut weld due to improper start-up of the welding. For future study other parameters and optimization technics need to be considered. The parameter combination must reflect safety, environment issue and reasonable factors.